Persepsi Korban Love Scamming Di Media Sosial - Novema Kumalasari; Sri Herwindya Baskara Wijaya (Universitas Sebelas Maret (UNS), 2024)
Love scamming that occurs through social media is increasingly troubling, especially for women who are vulnerable to forms of violence. This study aims to determine the perceptions of love scamming victims about the information manipulation tactics applied by the perpetrators in Semarang City through social media. This research uses descriptive qualitative method, with sampling technique using purposive sampling. The theory used in this research is Interpersonal Deception Theory (IDT). The results of the study found that based on the overall perception of the victim, the perpetrator applied various kinds of information manipulation tactics to influence the emotional side and trust of the victim. This finding shows the importance of understanding the social interaction between the perpetrator and the victim during the love scam, to see what manipulation tactics the perpetrator usually uses until the scam is successful.